Enhanced Photodynamic Therapy by Reduced Levels of Intracellular Glutathione Obtained By Employing a Nano‐MOF with CuII as the Active Center. Issue 18 (23rd March 2018) - Zhang, Wei; Lu, Jun; Gao, Xiaonan; Li, Ping; Zhang, Wen; Ma, Yu; Wang, Hui; Tang, Bo
Abstract: In photodynamic therapy (PDT), the level of reactive oxygen species (ROS) produced in the cell directly determines the therapeutic effect. Improvement in ROS concentration can be realized by reducing the glutathione (GSH) level or increasing the amount of photosensitizer. However, excessive amounts photosensitizer may cause side effects. Therefore, the development of photosensitizers that reduce GSH levels through synergistically improving ROS concentration in order to strengthen the efficacy of PDT for tumor is important. We report a nano‐metal–organic framework (Cu II ‐metalated nano‐MOF {CuL‐[AlOH]2 } n (MOF‐2, H6 L=mesotetrakis(4‐carboxylphenyl)porphyrin)) based on Cu II as the active center for PDT. This MOF‐2 is readily taken up by breast cancer cells, and high levels of ROS are generated under light irradiation. Meanwhile, intracellular GSH is considerably decreased owing to absorption on MOF‐2; this synergistically increases ROS concentration and accelerates apoptosis, thereby enhancing the effect of PDT. Notably, based on the direct adsorption of GSH, MOF‐2 showed a comparable effect with the commercial antitumor drug camptothecin in a mouse breast cancer model. This work provides strong evidence for MOF‐2 as a promising new PDT candidate and anticancer drug. Abstract : Boosting photodynamic therapy : A metal–organic framework containing Cu II porphyrin is an effective additive for the photodynamic therapy of tumors. Levels of intracellular glutathione (GSH) are markedly decreased owing to absorption, leading to increasing concentrations of reactive oxygen species and accelerated apoptosis.